The Gene-Gene Interaction of INSIG-SCAP-SREBP Pathway on the Risk of Obesity in Chinese Children. (17th June 2014) - Liu, Fang-Hong; Song, Jie-Yun; Shang, Xiao-Rui; Meng, Xiang-Rui; Ma, Jun; Wang, Hai-Jun
Abstract : Background. Childhood obesity has become a global public health problem in recent years. This study aimed to explore the association of genetic variants in INSIG-SCAP-SREBP pathway with obesity in Chinese children. Methods. A case-control study was conducted, including 705 obese cases and 1, 325 nonobese controls. We genotyped 15 single nucleotide polymorphisms (SNPs) of five genes in INSIG-SCAP-SREBP pathway, including insulin induced gene 1 ( INSIG1 ), insulin induced gene 2 ( INSIG2 ), SREBP cleavage-activating protein gene ( SCAP ), sterol regulatory element binding protein gene 1 ( SREBP1 ), and sterol regulatory element binding protein gene 2 ( SREBP2 ). We used generalized multifactor dimensionality reduction (GMDR) and logistic regression to investigate gene-gene interactions. Results. Single polymorphism analyses showed that SCAP rs12487736 and rs12490383 were nominally associated with obesity. We identified a 3-locus interaction on obesity in GMDR analyses ( P = 0.001 ), involving 3 genetic variants of INSIG2, SCAP, and SREBP2 . The individuals in high-risk group of the 3-locus combinations had a 79.9% increased risk of obesity compared with those in low-risk group (OR = 1.799, 95% CI: 1.475–2.193, P = 6.61 × 10 - 9 ). Conclusion. We identified interaction of three genes in INSIG-SCAP-SREBP pathway on risk of obesity, revealing that these genes affect obesity more likely through a complex interaction pattern than single gene effect.